Delimitation of functional urban areas of supra-local importance for the purposes of spatial planning – on the example of the Łódzkie voivodeship - Bartosiewicz, Bartosz (Journal of Public Governance, 2016)
The subject of the paper is delimitation of functional urban areas for the purposes of regional spatial planning. The main objective is scientific description of the author’s own method of delimitating functional urban areas with the use of functional linkages between cities and their surroundings. All the analyses have been conducted on the four types of linkages: commuting to work and to school, ownership linkages of companies, and migrations, and shown on the example of urban settlement network in the Łódź region.